Evidence of Extreme Ultraviolet Superfluorescence in Xenon - Mercadier, L.; Benediktovitch, A.; Weninger, C.; Blessenohl, M. A.; Bernitt, S.; Bekker, H.; Dobrodey, S.; Sanchez-Gonzalez, A.; Erk, B.; Bomme, C.; Boll, R.; Yin, Z.; et al. (My University, 2019)
We present a comprehensive experimental and theoretical study on superfluorescence in the extreme ultraviolet wavelength regime. Focusing a free-electron laser pulse in a cell filled with Xe gas, the medium is quasi-instantaneously population inverted by 4d-shell ionization on the giant resonance followed by Auger decay. On the timescale of ∼10 ps to ∼100 ps (depending on parameters) a macroscopic polarization builds up in the medium, resulting in superfluorescent emission of several Xe lines in the forward direction. As the number of emitters in the system is increased by either raising the pressure or the pump-pulse energy, the emission yield grows exponentially over four orders of magnitude and reaches saturation. With increasing yield, we observe line broadening, a manifestation of superfluorescence in the spectral domain. Our novel theoretical approach, based on a full quantum treatment of the atomic system and the irradiated field, shows quantitative agreement with the experiment and supports our interpretation.